2013
DOI: 10.3797/scipharm.1208-13
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of Novel Antimicrobial and Anticancer Agents Among Tetrazolo[1,5-c]quinazoline-5-thione S-Derivatives

Abstract: The novel heterocyclization of 5-(2-aminophenyl)-1H-tetrazole with potassium ethylxanthogenate or carbon disulfide was proposed. The potassium salt of the tetrazolo[1,5-c]quinazoline-5-thione was subsequently modified by alkylation with proper halogen derivatives to (tetrazolo[1,5-c]quinazolin-5-ylthio)alkyls, N,N-dialkylethylamines, 1-aryl-2-ethanones, 1-(alkyl)aryl-2-ethanols, carboxylic acids, and esters. The structures of all newly synthesized compounds were confirmed by FT-IR, UV-vis, LC-MS, 1H, 13C NMR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The 4-chloroquinazolines 2a – c were, in turn, subjected to sodium azide in DMF at 45 °C and we isolated after 4 h the corresponding 5-styryltetrazolo[1,5- c ]quinazolines 3a – c by aqueous work-up and recrystallization ( Scheme 1 ). Previous studies on the 5-alkyl and 5-aryl substituted tetrazolo[1,5- c ]quinazolines have revealed that these compounds exist predominantly in the tetrazole form in both the solid state and solution phase [ 10 ]. However, the presence of an electron-withdrawing substituent such as a halogen atom in position 8 or 10 was found to result in spontaneous cleavage of the pyrimidine ring of the formed tetrazolo[1,5- c ]quinazoline into the corresponding N -3/5-halogeno-2-(1 H -tetrazolo-5-yl)phenyl)formamides [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…The 4-chloroquinazolines 2a – c were, in turn, subjected to sodium azide in DMF at 45 °C and we isolated after 4 h the corresponding 5-styryltetrazolo[1,5- c ]quinazolines 3a – c by aqueous work-up and recrystallization ( Scheme 1 ). Previous studies on the 5-alkyl and 5-aryl substituted tetrazolo[1,5- c ]quinazolines have revealed that these compounds exist predominantly in the tetrazole form in both the solid state and solution phase [ 10 ]. However, the presence of an electron-withdrawing substituent such as a halogen atom in position 8 or 10 was found to result in spontaneous cleavage of the pyrimidine ring of the formed tetrazolo[1,5- c ]quinazoline into the corresponding N -3/5-halogeno-2-(1 H -tetrazolo-5-yl)phenyl)formamides [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…The R 1 -2-(1 H -tetrazol-5-yl)anilines ( 1.1 – 1.5 ) were used as starting compounds and were obtained by known methods, described elsewhere [ 10 15 ]. Treatment of R 1 -2-(1 H -tetrazol-5-yl)-phenylamines with R 2 -phenylisocyanates was carried out under different conditions: heating with reflux in glacial acetic acid or stirring at room temperature also in acetic medium or alternatively in dioxane ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Substances 1.1–1.5 were synthesized according to the reported procedures [ 10 , 11 ]. Other starting materials and solvents were obtained from commercially available sources and used without additional purification.…”
Section: Methodsmentioning
confidence: 99%
“…Introduction of the 4-methoxyphenyl group at the 5 position of tetrazolo[1,5- c ]quinazoline-5-thione ( 46 ) resulted in the best antimicrobial agent among all the investigated substances. It even moderately inhibited the growth of Pseudomonas aeruginosa and Klebsiella pneumoniae [ 48 ]. Other research results showed that N -(4-(2-(2 H -tetrazol-5-yl)ethyl)-5-thioxo-4,5-dihydro-1,3,4-thiadiazol-2-yl)-benzamide ( 47 ) exhibited antimicrobial activity against Bacillus subtilis with a MIC value of 100 μg/mL compared with penicillin (31 μg/mL), against Pseudomonas aeruginosa with a MIC value of 125 μg/mL compared with penicillin (46 μg/mL), and against Streptomyces species with a MIC value of 125 μg/mL compared with penicillin (33 μg/mL) [ 49 ].…”
Section: Biological Activity Of Tetrazolium Derivativesmentioning
confidence: 99%